2019
DOI: 10.1002/ps.5646
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gut bacterial communities and their associations with host diets in four fruit borers

Abstract: BACKGROUND Microbiota that live in the gut of insects have a wide range of effects on host nutrition, physiology, and behavior. They may shape the adaptation of their hosts to different habitats and lifestyles. To characterize the gut microbiota of fruit borers comprehensively, we compared bacterial communities among Grapholita molesta, Conogethes punctiferalis, Carposina sasakii, and Cydia pomonella, which are serious lepidopteran pests. We selected G. molesta as a representative pest to more explicitly test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
98
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(114 citation statements)
references
References 65 publications
(129 reference statements)
15
98
1
Order By: Relevance
“…Enterococcus in gypsy moth L. dispar and spruce budworm Choristoneura fumiferana (Lepidoptera: Tortricidae) protects their hosts from Bacillus thuringiensis and grows normally in chlorpyrifos ethyl, lambda-cyhalothrin, spinosad, and lufenuron selective medium ( van Frankenhuyzen et al, 2010 ; Almeida et al, 2017 ), suggesting that they play a role in the tolerance to toxic substances. Liu et al (2019) found low abundance of Enterococcus in the gut of fifth-instar larvae of fruit-feeding G. molesta but higher abundance in shoot-feeding G. molesta , which was not consistent with our findings. We speculate that this may due to differences in diet or habitat.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Enterococcus in gypsy moth L. dispar and spruce budworm Choristoneura fumiferana (Lepidoptera: Tortricidae) protects their hosts from Bacillus thuringiensis and grows normally in chlorpyrifos ethyl, lambda-cyhalothrin, spinosad, and lufenuron selective medium ( van Frankenhuyzen et al, 2010 ; Almeida et al, 2017 ), suggesting that they play a role in the tolerance to toxic substances. Liu et al (2019) found low abundance of Enterococcus in the gut of fifth-instar larvae of fruit-feeding G. molesta but higher abundance in shoot-feeding G. molesta , which was not consistent with our findings. We speculate that this may due to differences in diet or habitat.…”
Section: Discussioncontrasting
confidence: 99%
“…Considering that the larval stage of Lepidoptera ingests a large number of plant materials and fruits, the microbes that are highly abundant in early-instar larvae may enable the host to better adjust to various environments, such as metabolizing insecticides or interfering with potentially pathogenic microbes present in its food. A previous work found that Proteobacteria, followed by Firmicutes, were the major phyla present in the gut of G. molesta larvae feeding on fruits or shoots ( Liu et al, 2019 ). Our study showed that Proteobacteria and Firmicutes were the dominant phyla at each life stage of G. molesta .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that the gut microbiota of PFM and OFM was dominated by Proteobacteria and Firmicutes, which is similar to the situation found in Y. Liu et al (25) and Y. Li et al (24), and in other lepidopterans such as Lymantria dispar , Helicoverpa armigera , and Bombyx mori (2629). However, there was a difference between PFM and OFM and other lepidopterans at the genus level.…”
Section: Discussionsupporting
confidence: 88%
“…The concealed lifestyle and wide range of host plant species used by these species make them useful to understand factors affecting their gut microbiota. Previous studies found that larvae of these two moths harbor a high diversity and richness of bacteria (24, 25), but it is not yet clear the two species are more likely to share the same gut microbores when they live in the same orchard and on the same host plant species.…”
Section: Introductionmentioning
confidence: 97%